Measuring effective taxation of housing Building the foundations for policy reform - Millar-Powell, Bethany (OECD Publishing, 2022)
This paper measures the effective taxation of housing investments in 40 OECD member and partner countries. The paper derives both Marginal Effective Tax Rates (METRs) and Average Effective Tax Rates (AETRs), which incorporate the stream of income and taxes over the life of the housing investment. The methodology is applied to owner-occupied and rented residential property for investments that are financed with debt or equity. The paper finds that the level and components of housing taxation depend greatly on the investment scenario. Effective tax rates vary substantially depending on the holding period, rate of return, tenure (owner-occupied or rented), financing scenario, and the inflation rate. Effective tax rates do not vary much with the taxpayer's income and wealth or with the rate of return. The paper finds there is scope to reduce the tax differential between different investment scenarios and strengthen progressivity and horizontal equity
Keywords: Taxation